The Effect of Red Dragon Fruit Juice on Blood Glucose Levels and Salivary pH in Type 2 Diabetes Mellitus Patients: A Quasi-Experimental Study - Meggy Wulandari Kai; Emilda Sari; Hilwatun Nisa (JURNAL CITRA KEPERAWATAN, 2026)
Type 2 diabetes mellitus (T2DM) is characterized by chronic hyperglycemia, leading to microvascular complications including xerostomia and altered salivary pH, which increase caries risk. While pharmacological management remains primary, side effects drive interest in complementary alternatives. Red dragon fruit (Hylocereus polyrhizus), rich in flavonoids and antioxidants, presents a potential adjunct therapy. This study evaluated the effect of red dragon fruit juice on random blood glucose levels and salivary pH in T2DM patients at a primary health center in Banjar, South Kalimantan. A quasi-experimental pre-test post-test control group design involved 30 participants (15 intervention, 15 control). Intervention group received 150 mL red dragon fruit juice daily for 7 days. Blood glucose and salivary pH were measured pre- and post-intervention. Wilcoxon signed-rank and Mann-Whitney tests were used for analysis. Intervention group showed significant reductions in blood glucose (p=0.003) and increases in salivary pH (p=0.000). Control group changes were non-significant (p=0.520, p=0.317). Red dragon fruit juice significantly lowered blood glucose and normalized salivary pH in T2DM patients. The effect is attributed to flavonoid-mediated improved insulin sensitivity and antioxidant reduction of oxidative stress on pancreatic beta-cells. This intervention offers a low-cost, accessible non-pharmacological strategy for T2DM self-management.